Analysis of the Influence of Mobile Banking on the Profitability Level of Sharia Banks in Indonesia in 2019-2023 - Sari, Indah; Siregar, Fitri Ana (Journal of Islamic Financial Technology, 2024)
The aim of this research is to determine the effect of mobile banking on the level of Return On Assets (ROA) of Islamic banks in Indonesia in 2019-2023. The rise and fall of ROA is caused by unstable profits and total assets. This research uses quantitative research, and the data source uses secondary data in the form of a time series of 20 samples. Data analysis techniques use descriptive statistical test techniques, normality test, hypothesis test (t test), coefficient of determination test (R Square), and simple linear regression analysis. Data processing uses the SPSS Version 23 program. The research results show that the mobile banking variable has a partial effect on the profitability of Islamic banks in Indonesia in 2019-2023. This can be proven by the results of the t test analysis showing that the e-banking variable has t count gt; t table, thus e-banking has an effect on the profitability of Islamic banks in Indonesia in 2019-2023.Keywords: Mobile Banking, Profitability